Badan Pengawas Rumah Sakit (BPRS) Sebagai Badan Penyelesaian Sengketa Medik Secara Mediasi - Supeno Supeno (Universitas Batanghari Jambi, 2022)
In Article 60 of Law Number 44 of 2009 concerning Hospitals it is regulated that one of the duties of the Hospital Supervisory Board is to receive complaints and resolve disputes through mediation while the membership of a Provincial BPRS consists of elements of the government, professional organizations, hospital associations, and community leaders. . The purpose of this study was to assess the elements of professional organizations as members of the BPRS, the type of research used was normative juridical using a statutory approach, the results showed that the membership structure of the BPRS from the elements of professional organizations was not neutral, independent and impartial, the principle of mediation that a mediator is required to be able to act neutrally, independently and impartially, thus professional organizations as one of the elements of a BPRS to resolve medical disputes through mediation need to be reviewed.